Prenatal Care for American Indian Women. Issue 4 (July 2020) - Johnson, Mary Beth
Abstract : Abstract: Early and regular prenatal care, which aims to prevent and identify complications associated with pregnancy, birth, and newborn health, is associated with improved health of pregnant women and their infants. American Indian/Alaska Native (AI/AN) women are at risk for pregnancy, birth, and newborn health complications associated with health disparities including poverty, lower educational levels, limited access to healthcare, and adverse childhood events. American Indian/Alaska Native women in the United States experience barriers specifically related to prenatal care, including lack of access, dissimilar communication styles, and inconsistent continuity of care. Culturally appropriate prenatal care should be provided to reduce maternal and newborn morbidity and mortality. Community-based interventions such as home visiting, that may potentially improve prenatal care, focusing on the American Indian tribes of the Northern Great Plains, specifically North Dakota, are discussed. Abstract : American Indian women face many challenges in accessing maternal and infant care during pregnancy, birth, and postpartum. A review of the evidence is presented with suggestions for home visits as a potential solution to improve maternity care access and enhance outcomes.